Extracorporeal shock wave lithotripsy of gall stones: an in vitro comparison between an electrohydraulic and a piezoceramic device. Issue 3 (March 1991) - Schachler, R; Bird, N C; Sauerbruch, T; Frost, E A; Sackmann, M; Paumgartner, G; Johnson, A G
Abstract : A comparative study of the effectiveness of two types of lithotripter in fragmenting gall bladder stones is reported. The machines used were a Piezolith 2300, which generates shock waves by the piezoceramic principle, and a Dornier MPL 9000, which produces the shock waves by underwater spark discharge. With each machine, corresponding stones of 45 pairs of weight and volume matched calculi (median volume 0.5 cm3, median diameter 10.5 mm) obtained at cholecystectomy were treated. All stones were successfully disintegrated (fragments smaller than 2 mm) with up to 5400 (median 628) shocks with the Piezolith and 3450 (median 428) shocks with the MPL 9000 lithotripters. With the Piezolith, operating at the highest power setting, a 1.65 fold median higher number of shocks was required for stone fragmentation than with the MPL 9000 at a medium power setting. Stone volume seemed to be the only determinant which affected ease of fragmentation; composition and density of the stones as assessed by computed tomography did not seem to be governing factors.